KATA BENDA DALAM BAHASA INGGRIS DAN BAHASA MONGONDOW SUATU ANALISIS KONTRASTIF - TUNGKAGI, MENTARI D.U (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2015)
ABSTRACT This research entitled â€œKata Benda dalam Bahasa Inggris dan Bahasa Mongondow (Suatu Analisis Kontrastif)â€. The objects of the research are to identify and classify the kinds and functions of nouns in English and Mongondownese language. The writer used the concept by Thomson and Martinet (1986), and analyzed them by using contrastive analysis to find out the differences based on the theory of Lado (1971). The English data for this research were taken from some grammatical books and Mongondownese data were taken by some informants who speak Mongondow language well. The result shows that there are differences between the function of nouns in English and Mongondow language in terms of function on possessive case. The possessive form in English attach to the subject, but the possessive case in Mongondow language has its own word. Keywords: Nouns in English and Bolaang Mongondow Language: A Contrastive Analysis